Inter-Cultural Policies in Higher Education in Mexico: Are There Inter-Cultural Professions? - Patricia Medina Melgarejo (Universidad Pedagógica Nacional, 2013)
This article presents a recount of experiences of schooling and education of Indian professional people in Latin America and Mexico and about the different ways they have been acquired from the nineties of past century to the first decade of twenty first one. In this research the journey of policies of intercultural Indian higher education in Mexico and their configuration in contrast to intercultural higher education in Latin America is showed.